PENGARUH BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Tundjung, Ghafara Mawaridi Mazini; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2015)
This  study  aims  to  examine  the  effect  of  deferred  tax  expense  on  the  earningsmanagement case study in manufactured listed companies in Indonesia Stock Exchange. While financial restatement are measured using dummy variable which used “1” if the firm ply earnings management and “0” if the firm ply non-earnings management. This study also tests several control variables namely firm size, leverage, growth.Data for this study are obtained from annual report of companies listed on Indonesia Exchange Stock (BEI) in 2011-2013. Sampling using purposive sampling method, the sample  is  selected  using certain  considerations  that  are tailored  to the purpose  of  research  or  study  problems  developed  so  that  the  sample  in  this  study amounted to 55 companies in the third period of the study to 1655 companies.  The hypothesis testing use logistic regression analysis.The results showed that the Deferred tax expense significant positively affects the earnings management, While discretionary accrual did not significantly affects the Earnings Management